2003
DOI: 10.1002/j.1556-6978.2003.tb01814.x
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and Retention of Ethnic Minority Counselor Educators: An Exploratory Study of CACREP‐Accredited Counseling Programs

Abstract: This exploratory study sought to determine the strategies used by programs accredited by the Council for Accreditation of Counseling and Related Educational Programs (CACREP) to recruit and retain ethnic minority faculty. Seventy‐three CACREP liaisons were surveyed, and the results indicated that many programs have not developed specific strategies to recruit and retain ethnic minority faculty. Mentoring was the most frequently reported strategy for retaining ethnic minority faculty. Implications for counselor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 20 publications
(21 reference statements)
1
25
1
Order By: Relevance
“…Several participants acknowledged needing help regarding the interview process, not understanding the difference between a clinical interview and an academic interview, and not knowing how to prepare for interviews. Borders et al (), Holcomb‐McCoy and Bradley (), and Salazar, Herring, Cameron, and Nihlen () all reported that underrepresented counselor education faculty did not receive the same level of mentorship as those from majority cultural groups. Gaps in mentorship for students of color applying for academic positions may help the counseling profession to understand and thereby address disparities in representation of faculty from marginalized populations among tenured professors and administrative positions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several participants acknowledged needing help regarding the interview process, not understanding the difference between a clinical interview and an academic interview, and not knowing how to prepare for interviews. Borders et al (), Holcomb‐McCoy and Bradley (), and Salazar, Herring, Cameron, and Nihlen () all reported that underrepresented counselor education faculty did not receive the same level of mentorship as those from majority cultural groups. Gaps in mentorship for students of color applying for academic positions may help the counseling profession to understand and thereby address disparities in representation of faculty from marginalized populations among tenured professors and administrative positions.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents from 26 (36%) of the surveyed programs articulated a specific plan or strategy for recruiting underrepresented faculty. Thus, the researchers found that most of the programs were not able to produce evidence of particular steps they took in order to attract a wide array of candidates (Holcomb‐McCoy & Bradley, ). Although the Holcomb‐McCoy and Bradley () study is dated, we were unable to locate subsequent investigations and so it remains an important resource.…”
Section: Diversity and Hiring Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, researchers have surveyed job satisfaction and perceptions of racial climate (Holcomb-McCoy and Addison-Bradley 2005), and recruitment and retention strategies (Holcomb-McCoy and Bradley 2003). Brinson and Kottler (1993) explored cross-cultural mentoring as a retention strategy, providing recommendations to aid minority faculty in gaining support from White colleagues.…”
mentioning
confidence: 99%